Preliminary investigation of a hypertonic saline nasal rinse as a hygienic intervention in dairy workers. Issue 1 (2nd January 2023) - Erlandson, Grant; Magzamen, Sheryl; Sharp, Julia L.; Mitra, Sanchayita; Jones, Kenneth; Poole, Jill A.; Bradford, Mary; Nonnenmann, Matthew; Reynolds, Stephen J.; Schaeffer, Joshua W.
Abstract: Livestock workers experience an increased burden of bioaerosol-induced respiratory disease including a high prevalence of rhinosinusitis. Dairy operations generate bioaerosols spanning the inhalable size fraction (0–100 μm) containing bacterial constituents such as endotoxin. Particles with an aerodynamic diameter between 10 and 100 μm are known to deposit in the nasopharyngeal region and likely affect the upper respiratory tract. We evaluated the effectiveness of a hypertonic saline nasal lavage in reducing inflammatory responses in dairy workers from a high-volume dairy operation. Inhalable personal breathing zone samples and pre-/post-shift nasal lavage samples from each participant over five consecutive days were collected. The treatment group (n = 5) received hypertonic saline while the control group (n = 5) received normotonic saline. Personal breathing zone samples were analyzed for particulate concentrations and endotoxin using gravimetric and enzymatic methods, respectively. Pro- and anti-inflammatory cytokines (i.e., IL-8, IL-10, and TNF-α) were measured from nasal lavage samples using a multiplex assay. Inhalable dust concentrations ranged from 0.15 to 1.9 mg/m 3 . Concentrations of both pro- and anti-inflammatory cytokines, specifically IL-6, IL-8, and IL-10, were significantly higher in the treatment group compared to the control group ( p < 0.02, p < 0.04, and p < 0.01, respectively). Further analysis of IL-10 anti-inflammatory indicates a positive association between hypertonic saline administration and IL-10 production. This pilot study demonstrates that hypertonic saline nasal lavages were successful in upregulating anti-inflammatory cytokines to support larger interventional studies.